2019
DOI: 10.1111/pere.12278
|View full text |Cite
|
Sign up to set email alerts
|

Romantic attachment, dyadic coping, and parental adjustment across the transition to parenthood

Abstract: This study explored the mediating role of common dyadic coping (common DC) on the longitudinal associations between attachment‐related anxiety and avoidance and parental adjustment to the first year postpartum. A total of 92 Portuguese couples completed self‐report questionnaires of romantic attachment, common DC, parenting stress, and parental confidence. Results showed that more avoidant parents (at mid‐pregnancy) engaged less in common DC (at 6 weeks postpartum), which consequently increased their partner's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 62 publications
2
20
1
4
Order By: Relevance
“…These findings come to challenge the traditional role of fathers as the support provider and mothers as the care recipients (Darwin et al, 2017), highlighting that women and men benefitted mostly and equally from joint coping strategies regarding numerous dimensions of life. This adds on recent perinatal research suggesting that common DC is a key resource for partners' relationship satisfaction (Molgora et al, 2019) and confidence in their parental role and against parenting stress (Alves et al, 2019). However, contrary to these studies, we found actor but not partner effects between common DC and partners' adjustment (which did not confirm our hypothesis 2b).…”
Section: Discussioncontrasting
confidence: 99%
“…These findings come to challenge the traditional role of fathers as the support provider and mothers as the care recipients (Darwin et al, 2017), highlighting that women and men benefitted mostly and equally from joint coping strategies regarding numerous dimensions of life. This adds on recent perinatal research suggesting that common DC is a key resource for partners' relationship satisfaction (Molgora et al, 2019) and confidence in their parental role and against parenting stress (Alves et al, 2019). However, contrary to these studies, we found actor but not partner effects between common DC and partners' adjustment (which did not confirm our hypothesis 2b).…”
Section: Discussioncontrasting
confidence: 99%
“…In line with prior research (Alves et al., ; Alves et al, ; Brandão et al., ; Molgora et al., ), our findings reinforce the idea that perinatal intervention approaches should include a DC component and efforts should be made to encourage both women's and men's participation as both seem to be influenced by these dyadic processes. While preventive interventions aimed to promote stress management within couples already included a component focusing on the promotion of equity in DC (e.g., Couples Coping Enhancement Training [CCET]; Bodenmann & Shantinath, ), our findings suggest important refinements of existing approaches.…”
Section: Conclusion and Implications For Clinical Practicesupporting
confidence: 91%
“…Existing studies that have focused on the role of the couple's relationship during the transition to parenthood have privileged an individual approach (Mickelson & Biehle, ), mostly considering the woman's perspective and adjustment (Pilkington et al., ). A couple‐based approach that considers the couple as the unit of analysis, including both self and partner characteristics simultaneously, has been the focus of recent studies (e.g., Alves, Fonseca, Canavarro, & Pereira, ; Alves, Milek, Bodenmann, Fonseca, Canavarro, & Pereira, ; Molgora et al., ; Schoppe‐Sullivan et al., ), some of which have examined the influence of couple‐level factors on partners’ adjustment (e.g., couples’ congruence in marital relationship quality; Gameiro, Nazaré, Fonseca, Moura‐Ramos, & Canavarro, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…dyadic coping) may buffer detrimental effects of TTP [19]. A meta-analysis, not specific to the TTP, documents the importance of dyadic coping for relationship satisfaction [20] and it has also been shown to be predictive for partner's parenting stress during the TTP [21]. Similarly, couples' communication is a powerful predictor of relationship satisfaction and mediates the effects of stress on the relationship [22].…”
Section: Relevance Of Relational Skills For Relational Well-beingmentioning
confidence: 97%